Prospective investigation of risk factors for prostate cancer in the UK Biobank cohort study - Perez-Cornago, A; Key, T; Allen, N; Fensom, G; Bradbury, K; Martin, R; Travis, R (Springer Nature, 2017)
Prostate cancer is the most common cancer in British men but its aetiology is not well understood. We aimed to identify risk factors for prostate cancer in British males.We studied 219 335 men from the UK Biobank study who were free from cancer at baseline. Exposure data were collected at recruitment. Prostate cancer risk by the different exposures was estimated using multivariable-adjusted Cox proportional hazards models.In all, 4575 incident cases of prostate cancer occurred during 5.6 years of follow-up. Prostate cancer risk was positively associated with the following: black ethnicity (hazard ratio black vs white=2.61, 95% confidence interval=2.10-3.24); having ever had a prostate-specific antigen test (1.31, 1.23-1.40); being diagnosed with an enlarged prostate (1.54, 1.38-1.71); and having a family history of prostate cancer (1.94, 1.77-2.13). Conversely, Asian ethnicity (Asian vs white hazard ratio=0.62, 0.47-0.83), excess adiposity (body mass index (⩾35 vs <25 kg m-2=0.75, 0.64-0.88) and body fat (⩾30.1 vs <20.5%=0.81, 0.73-0.89)), cigarette smoking (current vs never smokers=0.85, 0.77-0.95), having diabetes (0.70, 0.62-0.80), and never having had children (0.89, 0.81-0.97) or sexual intercourse (0.53, 0.33-0.84) were related to a lower risk.In this new large British prospective study, we identified associations with already-established, putative and possible novel risk factors for being diagnosed with prostate cancer. Future research will examine associations by tumour characteristics.